2006
DOI: 10.1186/1471-2466-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Association between anemia and quality of life in a population sample of individuals with chronic obstructive pulmonary disease

Abstract: Background: Several studies investigated the association of anemia with health related quality of life (HRQL) in patients with chronic disease. However, there is little evidence regarding the association of anemia with HRQL in patients with chronic obstructive pulmonary disease (COPD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 23 publications
9
56
0
5
Order By: Relevance
“…We found only one study (conducted in the USA) in which the hemoglobin levels of COPD patients correlated positively with the physical components of the SF-36 (r 2 = 0.0850; p = 0.003). (27) A study conducted in Brazil and involving renal failure patients on hemodialysis also showed that decreased hemoglobin levels correlated with pain (r = 0.22; p = 0.018), (28) suggesting that, regardless of the type of disease, low hemoglobin levels can increase the levels of bodily pain.…”
Section: Discussionmentioning
confidence: 99%
“…We found only one study (conducted in the USA) in which the hemoglobin levels of COPD patients correlated positively with the physical components of the SF-36 (r 2 = 0.0850; p = 0.003). (27) A study conducted in Brazil and involving renal failure patients on hemodialysis also showed that decreased hemoglobin levels correlated with pain (r = 0.22; p = 0.018), (28) suggesting that, regardless of the type of disease, low hemoglobin levels can increase the levels of bodily pain.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies addressing the importance of Hb and/or Hc in COPD have focused on the common definitions of anemia and polycythemia, [32][33][34] despite the fact that the respective cutoff values have never been validated with regard to their prognostic value in COPD. To evaluate the clinical impact of Hb levels in detail and to answer the question whether there is an optimal threshold and where it is, we checked all percentiles of Hb and found optimal cutoff values of 14.3 g/dL for females and 15.1 g/dL for males for predicting long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…The level of haemoglobin is strongly and independently associated with increased functional dyspnoea and decreased exercise capacity, and is therefore an important contributor to functional capacity as well as a poor quality of life [115,117]. In some studies, anaemia is an independent predictor of mortality [118].…”
Section: Arterial Stiffness and Endothelial Functionmentioning
confidence: 99%